2014
DOI: 10.1007/s11274-014-1706-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pncA mutations in pyrazinamide-resistant Mycobacterium tuberculosis isolates from Korea and analysis of the correlation between the mutations and pyrazinamidase activity

Abstract: To investigate the effect of natural pyrazinamidase (PncA) mutations on protein function, we analyzed expression and PncA activity of eight pncA point mutants identified in nineteen pyrazinamide-resistant Mycobacterium tuberculosis clinical isolates. Among them, two mutants (Y99D and T135P) showed high expression level and solubility comparable to those of the wild-type PncA protein, two (K48E and G97D) displayed low expression level and solubility, and four (C14R, H51P, W68S, and A146V) were insoluble. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
2
18
0
2
Order By: Relevance
“…Thus, loss-of-function mutations in pncA represent the primary mechanism of PZA resistance in clinical isolates. Diverse pncA mutations, including single and multi-nucleotide polymorphisms and indels, have been reported in PZA resistant clinical isolates along the entire 561 base pair gene length [26,27] . Recently, Yadon et al [28] created a comprehensive library of PncA polymorphisms through saturating mutagenesis and identified over 300 substitutions, some of which were previously reported in clinical isolates, that conferred PZA resistance in vitro and in vivo.…”
Section: Proposed Molecular Targets For Pzamentioning
confidence: 99%
“…Thus, loss-of-function mutations in pncA represent the primary mechanism of PZA resistance in clinical isolates. Diverse pncA mutations, including single and multi-nucleotide polymorphisms and indels, have been reported in PZA resistant clinical isolates along the entire 561 base pair gene length [26,27] . Recently, Yadon et al [28] created a comprehensive library of PncA polymorphisms through saturating mutagenesis and identified over 300 substitutions, some of which were previously reported in clinical isolates, that conferred PZA resistance in vitro and in vivo.…”
Section: Proposed Molecular Targets For Pzamentioning
confidence: 99%
“…10,[15][16][17] However, Yoon et al 18 reported that mutations at another site may affect the activity of the protein by altering the expression level or the folding effect. 18 In the current study, we performed PZA drug susceptibility testing followed by the sequencing of the pncA gene, which showed some novel mutations that were found to be associated with resistance (under review in BMC (BioMed central) infectious disease). The sequences were submitted in the GeneBank (Accession No MH461111-17).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the mechanism of action of PZA remains partially unknown, the primary mechanism of PZA resistance in clinical isolates is well established (4,5). Because PZA is a prodrug that requires conversion to pyrazinoic acid (POA) for its antimicrobial effect, mutations of the gene encoding the mycobacterial PncA amidase (pncA) result in PZA resistance (4)(5)(6)(7). Approximately 78% of PZA-resistant isolates harbor mutations in pncA (3).…”
mentioning
confidence: 99%